FAKTOR-FAKTOR YANG MEMPENGARUHI KEPATUHAN MASYARAKAT DALAM MEMBAYAR IURAN PADA PROGRAM JAMINAN KESEHATAN NASIONAL (JKN) DI INDONESIA: LITERATURE REVIEW - Putri Safira; Salsabilla, Shelly Safira Maulia Harahap, Fitriani Pramita Gurning (Jurnal Kesehatan, 2024)
The JKN program is to ensure equal access to high-quality health services for all Indonesian citizens, offering extensive coverage at affordable rates. Despite the numerous advantages provided by the JKN Program, some participants fail to adhere to the regulations, such as delays in contribution payments. This study seeks to identify the factors influencing the level of compliance among communities regarding contributions to the JKN Program across various regions in Indonesia. Employing a literature review design, the researcher collects relevant and reliable research articles. Subsequently, these articles are thoroughly reviewed to generate new analyses. The findings of this study suggest that community compliance with JKN program contributions is influenced by factors such as income, knowledge, education, family size, perceptions of health services, and employment.